Sugarcane bagasse ash for fipronil removal - Barbosa, Larissa M. S. [UNESP]; Baêta, Bruno E. L.; de Barros, André Luis Corrêa; Braga Almeida, Marys L.; Libânio, Marcelo (IWA Publishing, 2023)
Adsorbents were studied for removing fipronil, a pesticide, from water. The study included sugarcane bagasse fly ash (SBFA) and traditional activated carbon. SBFA was characterized by X-ray fluorescence, specific mass determination, electron microscopy, particle size analysis and zeta potential. The results showed that, without prior treatment, its removal efficiency for fipronil was 80% with 2 h contact time, which is much higher than reported in other studies. SBFA’s zeta potential was 8.02. In low pH systems, fipronil adsorption is expected to be even more efficient, as the molecule presents both the amino group (NH) and Cl, which may favor adsorbent surface interactions by giving rise to polar electrostatic forces. The Freundlich model (R2 = 0.9290) describes the adsorption data better than the Langmuir model (R2 = 0.8870). The method developed for fipronil adsorption is low-cost and enables the reuse of sugarcane industry waste.
Keywords: adsorption; alternative adsorbents; fipronil; pesticide removal; sugarcane bagasse fly ash; water treatment